Successful pervaginal management of Schistosoma reflexus in buffalo: A case report - Yadav, Brijesh Kumar; Gangwar, Kavisha; Agrawal, Jitendra Kumar; Saxena, Atul (Buffalo Bulletin, 2024)
The present case reports the successful per-vaginal delivery of Schistosoma reflexus fetus using Thygeson’s fetotome. A nine-year-old Murrah buffalo of the sixth parity with an extended gestation period (11 months) was presented to the TVCC Mathura with a history of birth difficulties. The case was previously examined by a local veterinarian and tearing of the uterus, rectum and bowel was observed by him. The animal has been treated with antimicrobial, anti-inflammatory, antihistamines, multivitamins, and intrauterine therapy is using a tetracycline bolus. The animal is uneventfully recovered after 3 days of treatment.